Generic intertextuality in online social activism: The case of the It Gets Better project. (25th June 2015) - Jones, Rodney H.
Abstract The It Gets Better project has been held up as a model of successful social media activism. This article explores how narrators of It Gets Better videos make use of generic intertextuality, strategically combining the canonical narrative genres of the exemplum, the testimony, and the confession in a way that allows them to claim 'textual authority' and to make available multiple moral positions for themselves and their listeners. This strategy is further facilitated by the ambiguous participation frameworks associated with digital media, which make it possible for storytellers to tell different kinds of stories to different kinds of listeners at the same time, to simultaneously comfort the victims of anti-gay violence, confront its perpetrators, and elicit sympathy from 'onlookers'. This analysis highlights the potential of new practices of online storytelling for social activism, and challenges notions that new media are contributing to the demise of common narrative traditions. (Activism, digital media, genre, LGBT discourse, narrative, positioning)*